Analisis Sistem Royalti antara Penulis dan Penerbit dalam Mendukung Pengelolaan Sumber Daya Intelektual untuk Pengembangan Pendidikan Islam Perspektif Ekonomi Syariah (Studi pada CV. Al Mannaf Pustaka Pekanbaru) - Landes Yuanda; Delima Afriyanti; Febri Kusuma; Maya Eka Rahma Sari (Institut Agama Islam Hidayatullah Batam, 2026)
Royalties are understood as a form of remuneration for the utilization of intellectual works that are commercialized by copyright users. Although the concept of royalties is not yet widely understood by the general public, it has long been practiced within the book publishing and printing industry. This study aims to analyze royalties as an instrument for managing intellectual resources from the perspective of Islamic economics, using a case study of CV. Al Mannaf Pustaka Pekanbaru, a publishing house oriented toward the application of Islamic law principles. This research employs a qualitative approach with a case study method, conducted in depth through observation, interviews, and documentation of relevant books and scholarly works. The findings reveal that the relationship between authors and the publisher at CV. Al Mannaf Pustaka Pekanbaru is based on two types of contracts, namely the contract for solo quote book writing classes and the manuscript printing contract, both of which can be categorized as ijarah al-asykhas contracts. In addition, there are contractual arrangements between the author or publisher and buyers, which are classified as istishnaʿ contracts. The royalty system implemented is identified as ujrah (wages or remuneration) for the services and intellectual contributions of the author and is found to comply with the principles of Islamic economics, as it does not contain elements prohibited by Sharia, such as riba, gharar, haram, batil, or maisir. Thus, royalties function not only as an economic mechanism but also as a fair, transparent instrument for managing intellectual resources in accordance with Sharia values.